Endocrine Disruptor Compounds—A Cause of Impaired Immune Tolerance Driving Inflammatory Disorders of Pregnancy? - Schjenken, John E.; Green, Ella S.; Overduin, Tenuis S.; Mah, Chui Yan; Russell, Darryl L.; Robertson, Sarah A. (Frontiers in Endocrinology, 2021)
Endocrine disrupting compounds (EDCs) are prevalent and ubiquitous in our environment and have substantial potential to compromise human and animal health. Amongst the chronic health conditions associated with EDC exposure, dysregulation of reproductive function in both females and males is prominent. Human epidemiological studies demonstrate links between EDC exposure and infertility, as well as gestational disorders including miscarriage, fetal growth restriction, preeclampsia, and preterm birth. Animal experiments show EDCs administered during gestation, or in either parent prior to conception, can interfere with gamete quality, embryo implantation, and placental and fetal development, with consequences for offspring viability and health. It has been assumed that EDCs operate through disrupting hormone-regulated events in reproduction and fetal development, but EDC effects on maternal immune receptivity to pregnancy are also implicated. EDCs can modulate both the innate and adaptive arms of the immune system, to alter inflammatory responses, and interfere with generation of regulatory T (Treg) cells that are critical for pregnancy tolerance. Effects of EDCs on immune cells are complex and likely exerted by both steroid hormone-dependent and hormone-independent pathways. Thus, to better understand how EDCs impact reproduction and pregnancy, it is imperative to consider how immune-mediated mechanisms are affected by EDCs. This review will describe evidence that several EDCs modify elements of the immune response relevant to pregnancy, and will discuss the potential for EDCs to disrupt immune tolerance required for robust placentation and optimal fetal development.